ANALYSIS OF DIFFERENCES IN LIFESTYLE AND HALAL AWARENESS PERCEPTION OF MOSLEM AND NON-MOSLEM WARDAH CONSUMERS - Luliani Nur Maulida; Reny Fitriana Kaban (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to analyse the differences in perception between two Wardah consumers, namely Moslem and non-Moslem by using the independent variables of lifestyle and halal awareness. The sampling technique used for getting the respondents in this research was purposive sampling. The data analysis method used in this study was the Mann-Whitney non-parametric statistical difference test. The results showed that there were no significant differences in lifestyle perceptions between Moslem and non-Moslem consumers, and there were significant differences in perceptions of halal awareness between Moslem and non-Moslem consumers. It is recommended for Wardah management to intensively socialize the urgency of halal products to both types of consumers when they want to buy cosmetics.